2012
DOI: 10.1002/ejic.201200282
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity of PtIIComplexes with Carboxylated Phosphanes in Chelated or Ring‐Opened Forms

Abstract: The biological activity of four cisplatin-like Pt-phosphane complexes, namely, cis-[PtCl 2 (L) 2 ], L = PPh 3 , P(Ph) 2 (p-C 6 H 4 -COOH), P(Ph) 2 (-CH 2 CH 2 -COOH) and its succinimidyl ester derivative, has been tested on monolayer cultures of three tumour cell lines (namely, A2780 human ovarian carcinoma and its cisplatin-resistant form A2780Cp8, and human colon adenocarcinoma HCT116). These complexes can undergo intramolecular rearrangements by virtue of their functionalized phosphanes, thereby existing as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…Intermolecular oxidative addition has been extensively studied on square-planar platinum(II) compounds and it is generally observed that the set of equatorial ligands of the resulting platinum(IV) compounds retain the stereochemistry of the starting platinum(II) compound while the new ligands occupy the axial positions.23,24 Intermolecular oxidative addition on coordination compounds such as cisplatin, carboplatin and their analogues is often the method of choice to prepare platinum(IV) prodrugs with the most widely used oxidizing agents being halogens or hydrogen peroxide. [25][26][27][28][29][30][31] Oxidative addition reactions on cyclometallated platinum(II) compounds have received less attention and often involve reagents such as methyl iodide. [32][33][34][35] In this work, the oxidative addition of both methyl iodide and iodine to several cyclometallated platinum(II) compounds was studied with the purpose of developing a systematic method to prepare novel octahedral cyclometallated platinum(IV) compounds potentially useful as antitumor agents.…”
Section: Introductionmentioning
confidence: 99%
“…Intermolecular oxidative addition has been extensively studied on square-planar platinum(II) compounds and it is generally observed that the set of equatorial ligands of the resulting platinum(IV) compounds retain the stereochemistry of the starting platinum(II) compound while the new ligands occupy the axial positions.23,24 Intermolecular oxidative addition on coordination compounds such as cisplatin, carboplatin and their analogues is often the method of choice to prepare platinum(IV) prodrugs with the most widely used oxidizing agents being halogens or hydrogen peroxide. [25][26][27][28][29][30][31] Oxidative addition reactions on cyclometallated platinum(II) compounds have received less attention and often involve reagents such as methyl iodide. [32][33][34][35] In this work, the oxidative addition of both methyl iodide and iodine to several cyclometallated platinum(II) compounds was studied with the purpose of developing a systematic method to prepare novel octahedral cyclometallated platinum(IV) compounds potentially useful as antitumor agents.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, 3-(diphenylphosphino)propionic acid is able to function as a flexible hemilabile chelating system. [14][15][16][17] Here, both the carboxylic acid and phosphine functionality are able to coordinate with different bonding strength to a metal center (Scheme 2B), which is of high interest regarding the construction of organometallic catalysts. 7,[17][18][19] 3-(Diphenylphosphino)propionic acid has already been successfully applied as a bifunctional ligand for the construction of supramolecular structures as well as heterometallic complexes, applying different metal combinations.…”
Section: Introductionmentioning
confidence: 99%
“…In the former case, inactive ring closed/ active ring opened complexes have been proposed. [14][15][16][17][18][19] In the latter, the most important role is played by the octahedral Pt(IV) derivatives capable of being activated by reduction in vivo.…”
Section: Introductionmentioning
confidence: 99%